Diversidade genética de "rove beetles" Neotropicais da RPPN Alta da Figueira - Ciamponi, Guilherme Eduardo (Universidade Federal de São Carlos, 2025)
The Atlantic Forest is a biome of critical importance due to the richness of its biological diversity, underlining its high priority for the conservation of both known and yet-undescribed species. Conservation strategies for this biome include the establishment and maintenance of protected areas. One such initiative is the Alto da Figueira Private Natural Heritage Reserve (RPPN), which seeks to foster scientific research on its biological diversity, generating valuable data to inform conservation programs. The characterization of fauna belonging to the family Staphylinidae (order: Coleoptera), through combined morphological and molecular analyses, provides insights into the ecological integrity and conservation status of the reserve. A major challenge in studying this group is the difficulty of accurately identifying or confirming the taxonomic status of specimens. This is mainly due to the underrepresentation of nucleotide sequences from Neotropical taxa in databases, the lack of suitable taxonomic keys for species-level identification for these fauna and limited ecological knowledge of the group. In this study, 27 nucleotide sequences corresponding to the barcode region of the cytochrome c oxidase subunit I gene (COI marker) were generated from specimens that had been morphologically identified to the genus level. The main objectives were to: 1) assess the utility of the COI marker in supporting taxonomic identification; 2) evaluate its effectiveness for inferring phylogenetic relationships within the group; 3) increase the representation of Staphylinidae sequences in public repositories (BoLD and GenBank) and 4) associate the diversity of this fauna with the state of environmental preservation of the reserve. The identified taxa indicate that the conservation unit corresponds to a well-preserved forest in an advanced successional stage. Phylogenetic trees derived from the analyses of COI nucleotide sequences showed low resolution (despite high genetic variability). Similar results were obtained for a more conservative approach based on amino acid sequence comparisons. These findings emphasize the need to expand sampling efforts of this diverse beetle group to produce a more representative scenario of the biodiversity from the Atlantic Forest based on a more comprehensive and informative dataset that integrates morphological and molecular information.
Genetic diversity of Neotropical rove beetles in the Alto da Figueira Private Natural Heritage Reserve
Keywords: Atlantic Forest; Staphylinidae; RPPN Alto da Figueira; Protected Areas; Morphological Identification; Molecular Identification; Marcador Molecular; Mata Atlântica; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL